Campur Tangan Presiden Dalam Pemilihan Umum Presiden 2024 Dalam Editorial Tempo : (Analisis Wacana Kritis Norman Fairclough Pada Editorial Tempo Edisi 10 Januari 2024) - Aditya Ayu Putri; Farida Hariyati; Abdul Khohar (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The 2024 Indonesian presidential election becomes a contest to choose new presidential and vice-presidential candidates for the 2024-2029 period. Various methods are employed by each candidate pair to occupy the presidential seat in Indonesia. As known, media coverage of this presidential election has given rise to a discourse with multiple interpretations. The aim of this research is to analyze a discourse within critical discourse analysis to examine the construction built by Tempo media in depicting the president's image according to Norman Fairlough's critical discourse. This research employs a qualitative approach with content analysis method. The research findings indicate that Description: The news title reflects the President's role as a supporter of Prabowo Subianto. Interpretation: The President's actions indicate significant interference in the electoral process. Explanation: This discourse reproduces power structures and influences public perception of democracy. In conclusion, the importance of understanding discourse construction in news and its impact on public perception of the political process becomes evident, with emphasis on the need for the independence and neutrality of electoral institutions becoming more prominent.